Ethical dilemmas and conflicts in minor patients' care - general review - Andreea Salcudean; Marius-Catalin Cosma; Andreea-Georgiana Nan; Monica Kiss; Maria-Melania Lica (Cozma); Cristina-Raluca Bodo; Gabriela-Elena Strete (Amaltea Medical Publishing House, 2022)
The aim of this review study is to analyze and describe the main moral and ethical aspects regarding the minor patients's healthcare related procedures. The Pediatric Ethics differentiate from that of the competent adults, such particularities including surrogate decisions, confidentiality issues, genetic testing and research related matters, end-of-life situations and legal framework. An important aspect is that the child is not entirely lacking capacity, in fact, the literature underlines the importance of listening, analyzing and taking into consideration the minor patient's opinions, statements or judgements according to their age and cognitive development. The approach of the minor patient should always take into account the triad "doctor-parent-child" without neglecting any of the participants and their role. The main responsibility of the healthcare professionals is to act guided by the best interests of the minor patient.